Material characterization and axial crushing tests of single and double-walled columns at intermediate strain rates / Leonardo Gunawan … [et al.] - Leonardo Gunawan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2013)
This paper presents results of dynamic tensile tests of the St37 mild steel and dynamic axial impact tests of columns made of the same material. Both tests were performed in conjunction with the validation of numerical simulations of dynamic crushing of single and double-walled square columns. The tensile tests, which were performed at several strain-rates ranging from 0.001s1 to 100s1, provided the plastic flow stress data of the St37 mild steel that increases as the strain-rate increases. The dynamic axial crushing tests were conducted to single and double-walled square columns made of the St 3 7 mild steel. The test results indicate that the double-walled column has higher mean crushing force and larger energy absorbing capability than those of single-walled columns. Finite element simulations of the dynamic impact tests employing the flow stress data obtained from the tensile tests are in good agreements with those from the experiments. It is noted that the use of the strain-rate dependent material model of the St37 material improved the accuracy of the numerical simulations.